An Unusual and Severe Thyrotoxicosis in a Twin Pregnancy: Fortune Favors the Brave - Virginia Maltese; Elisa Gatta; Irene Silvestrini; Valentina Anelli; Francesca Bambini; Caterina Buoso; Maria Cavadini; Massimiliano Ugoccioni; Maura Saullo; Fiorella Marini; Elena Gandossi; Andrea Delbarba; et al. (Case Reports in Endocrinology)
Graves’ disease (GD) and gestational transient thyrotoxicosis (GTT) are the most common causes of thyrotoxicosis during pregnancy, with prevalence ranging from 0.1% to 1% and from 1% to 3%, respectively. Hyperthyroidism during pregnancy can have severe consequences if not promptly recognized and treated. Even more severe, if possible, is the thyroid storm, a life-threatening complication of hyperthyroidism, characterized by severe and dramatic clinical manifestations of thyrotoxicosis. No prior history of thyroid disease, absence of GD stigmata, negative thyrotropin (TSH) receptor antibody levels, serum human chorionic gonadotropin (hCG) higher on average, and symptoms of emesis may lead to the diagnosis of GTT. Few cases of thyroid storm during pregnancy are reported in literature, mainly due to gestational trophoblastic disease. We report a rare and severe case of thyroid storm in a 24-year-old woman at 15 weeks’ gestation with twins, likely due to GTT, precipitated by acute myocarditis. Initially presenting with weakness, vomiting, and sinus tachycardia, the patient rapidly deteriorated into a life-threatening condition characterized by hypokalemia, myocardial injury, and severe thyrotoxicosis. Cardiac imaging later revealed acute myocarditis. Thyroid function stabilized at the end of the pregnancy, allowing discontinuation of methimazole. Both fetuses were delivered via emergency cesarean section at 36 weeks, with no significant congenital abnormalities. This case highlights the complexity of diagnosing and managing hyperthyroidism in twin pregnancies, particularly in the context of hyperemesis gravidarum (HG).